Modern Problems of Mathematical Modeling, Computational Methods and Information Technologies: - Review, review (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2020)
Modern Problems of Mathematical Modeling, Computational Methods and Information Technologies: Materials of International scientific conference. – Rivne, 2018. – 317 p.